Influence of Marketing Strategies on Consumer Behaviour: A Study of Consumers of Paterson Zochonis (Pz) Cussons Nigeria Plc Kano - Abubakar, Magaji Adamu; Garba, Abdulkadir Rabiu (Kashere Journal of Management Sciences, 2024)
This paper seeks to determine the influence of marketing strategies on consumers’ behaviour. The study determines whether marketing strategies of PZ Cussons Nigeria PLC (Kano) have an influence on their consumers’ behaviour. This should make situational marketing strategies more clear which can lead to sustainable development through market segmentations. One way Analysis of Variance was used on the primary data that was collected by using questionnaires. The result shows that there is a positive and significant influence of marketing strategies of PZ Cussons Nigeria PLC (Kano) on their consumers’ behaviour; also pricing, packaging followed by advertisement is the order of importance of marketing strategies towards influencing consumers’ behaviours. It is recommended that the firm should not hesitate at its attempts on ensuring rewarding and efficient marketing strategy. A favourable environment should be designed, by marketing regulatory agencies, for manufacturing organizations to implement whatever strategic means they hope to adopt